2007
DOI: 10.1152/ajpendo.00263.2007
|View full text |Cite|
|
Sign up to set email alerts
|

Diet-induced modulation of mitochondrial activity in rat muscle

Abstract: Growing evidence supports the theory that mitochondrial dysfunction is an underlying cause of intramyocellular lipid (IMCL) accumulation and insulin resistance. Here, we hypothesized that high dietary fat (HF) intake could trigger changes in mitochondrial activity such that fatty acid oxidation is impaired in muscle and contributes to an elevation in intramyocellular lipid (IMCL) levels. Muscle mitochondrial activity was determined in vivo through measurement of the F1F0 ATP synthase flux, the terminal step in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
21
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 48 publications
4
21
0
Order By: Relevance
“…The duration of high-fat feeding also seems to differently affect mitochondrial function in skeletal muscle. In fact, oxidative phosphorylation was found increased after short-term (2-3 weeks) dietary treatment, but decreased after long-term treatment (Chanseaume et al 2007, Laurent et al 2007, Bonnard et al 2008). …”
Section: Mitochondrial Dysfunction In Insulin Resistancementioning
confidence: 95%
“…The duration of high-fat feeding also seems to differently affect mitochondrial function in skeletal muscle. In fact, oxidative phosphorylation was found increased after short-term (2-3 weeks) dietary treatment, but decreased after long-term treatment (Chanseaume et al 2007, Laurent et al 2007, Bonnard et al 2008). …”
Section: Mitochondrial Dysfunction In Insulin Resistancementioning
confidence: 95%
“…For example it has been reported that a high dietary fat intake can downregulate oxidative gene expression in muscle of humans and rodents [32], whereas more recent studies found that fat feeding increased fatty acid oxidation enzymes and mitochondrial fatty acid oxidative capacity [33 ,34 ]. Other reports do suggest changes in ATP production rates [35] and mitochondrial function after prolonged fat feeding [36 ] but not at the early time points (2-5 weeks) when muscle insulin resistance is already clearly evident in fat-fed rodents [1,37]. Thus it seems likely that there is an initial upregulation of both fatty acid clearance into muscle, and the subsequent ability to oxidize the fatty acids in insulin-resistant rodents, although presumably the latter is insufficient to prevent cytosolic lipid accumulation in the presence of a high fatty acid supply to muscle.…”
Section: Why Do Lipids Accumulate In Muscle?mentioning
confidence: 95%
“…However, the contributions of flux through the glycolytic enzymes GAPDH and PGK have been clearly demonstrated[5860]. These reactions are near equilibrium and thus large unidirectional fluxes far exceed flux through the F 1 F O ATPase and significantly contribute to the ST measurements without contributing to the net ATP synthesis[61]. The contributions from these near equilibrium glycolytic enzymes has been cited to explain the much higher ATP flux measurements from ST compared to those reported using other in vivo approaches[62, 63].…”
Section: In Vivo Approaches For Measuring Mitochondrial Phosphorylmentioning
confidence: 99%